Immunomodulation of Glycyrrhiza Polysaccharides In Vivo Based on Microbiome and Metabolomics Approaches - Yixuan Wu; Jie Sun; Wenjie Xie; Simin Xue; Xinli Li; Jianming Guo; Jinjun Shan; Guoping Peng; Yunfeng Zheng (Foods)
Glycyrrhiza uralensis Fisch. is a medicinal herb that can be added to food to provide therapeutic effects and reduce the burden of medications. Herein, the immunomodulatory effects of Glycyrrhiza polysaccharides (GPs) were verified and illustrated by intervening immunocompromised rats treated with different doses of GPs, which were reflected for adjusting the composition and structure of the intestinal microbiota and altering the metabolic profile. The immunomodulatory effects of GPs were exerted by regulating the intestinal microenvironment. In particular, GPs could promote the growth of probiotic bacteria Allobaculum, norank__o_Clostridia_UCG-014, Dubosiella, and g__norank_o___RF39 and curb the growth of harmful bacteria Enterococcus. The results showed that GPs had a prebiotic effect, which contributed to improving the intestinal environment and maintaining intestinal health. In addition, the content of beneficial differential metabolites was up-regulated, especially short-chain fatty acids, with alanine, aspartate, and glutamate metabolism; arginine biosynthesis; glyoxylate and dicarboxylate metabolism being the most enriched pathways. These metabolic pathways imply the metabolic process of GPs, and the metabolic pathways and differential effector metabolites of it are focused. Overall, the purpose of this article lies in providing support for the application of GPs for regulating immune function.